Assessing the sustainable nature of housing-related taxation receipts: The case of Ireland - Diarmaid Addison-Smyth; Kieran McQuinn (The Economic and Social Research Institute (ESRI), 2015)
Even by international standards, Ireland's fiscal position was particularly affected by the recent financial crisis. As budgetary surpluses quickly gave way to significant deficits post 2007, the deterioration in the Irish public finances culminated in an Excessive Deficit Procedure being launched in 2009 and entry into a formal EU/IMF assistance programme in late 2010. Much of this deterioration was caused by the sudden and sharp decline in the Irish housing market as property-related taxes dried up. In this paper we quantify the extent of housing related tax windfall gains and losses. We find that at various times over the past three decades, there have been instances where dis-equilibrium in the Irish housing market has had significant implications for the associated taxation receipts. Examining taxation aggregates in this manner can be seen as an important complement to recent policy responses aimed at improving fiscal governance.
Keywords: O40; O47; O16; 330; Fiscal; House Prices; Sustainable